Assessing intra-annual growth dynamics in climatically contrasting years, sites, and tree species using dendrometers and wood anatomical data - Debel, Annette; Foroozan, Zeynab; Häusser, Martin; Raspe, Stephan; Bräuning, Achim (Frontiers in Forests and Global Change, 2024)
Detecting the intra-annual dynamics and courses of secondary tree growth enables the accurate identification of crucial steps in the forming of a new tree ring. Furthermore, comparing the high-resolution recordings of tree growth with environmental conditions allows assessment of the influence of weather on wood formation processes. This study investigates the intra-annual growth performance of conifer species and European beech at two high- and two low-elevation sites in Bavaria, southeast Germany. We measured stem circumference changes with electronic band dendrometers and cambial dynamics by collecting microcores at biweekly intervals. We analyzed growth variations between the consecutive years 2020 and 2021, which showed distinct climatic differences during the growing seasons. While warm and dry conditions prevailed in spring and summer in 2020, spring in 2021 was comparatively cold, and summer precipitation was high. Different tree growth patterns were observed in the contrasting years 2020 and 2021. Distinct growth reductions occurred in the drier year 2020 for most of the studied tree species, while trees showed wider tree rings in 2021 despite of low growth rates at the beginning of the growing season. Climate-growth correlations exposed the intraseasonal influence of climatic conditions, particularly available soil water, water vapor pressure deficit, and soil temperature, on short-term tree responses. Wood anatomical analysis and daily stem diameter variations proved to be valid monitoring methods to assess individual wood formation processes and to identify species-specific tree responses to the influence of climatic conditions. However, combining both methods represents the most reliable approach due to the mutual ability to compensate for each other’s deficiencies. While dendrometers provided a very accurate and high-resolution record of intra-annual tree growth, wood anatomical analyses were more reliable in determining the exact onset and cessation of wood formation. For this reason, combining both is recommended for assessing prospective tree growth performance in the context of climate change.
Created from Fastlane, Scopus look-up
Keywords: dendrometer; Gompertz model; intra-annual growth dynamics; temperate forests; xylogenesis

BayTreeNet. Sprechende Bäume als Schnittstelle von Klimadynamik, Dendroökologie und Bildung für nachhaltige Entwicklung in Bayern. - Bräuning, Achim; Debel, Annette; Collier, Emily; Höhnle, Steffen; Mölg, Thomas; Schubert, Jan Christoph; Thieroff, Bernhard; Wehrmann, Sibille (Mitteilungen der Fränkischen Geographischen Gesellschaft, 2021)

Climate Signals for Growth Variations of F. sylvatica, P. abies, and P. sylvestris in Southeast Germany over the Past 50 Years - Debel, Annette; Meier, Wolfgang; Bräuning, Achim (Forests, 2021)
Since recent drought events have already caused severe damage to trees and droughts in the near future are expected to occur even more frequently, this study investigated the response of forest ecosystems to changing climate conditions in the topographically complex region of Bavaria, southeast Germany. For this purpose, climate–growth relationships of important European deciduous and coniferous tree species were investigated over the past 50 years at three middle mountain ranges and corresponding basins. A response analysis between tree-ring width and climate variables was applied to detect modifications in tree responses comparing two 25-year periods at individual forest sites. Furthermore, tree responses to climatic extreme years and seasons were analyzed using a superposed epoch analysis. The results showed that Scots pine (Pinus sylvestris) proved to be the most vulnerable and least drought-resistant of all investigated tree species. Likewise, Norway spruce (Picea abies) and European beech (Fagus sylvatica) revealed a higher drought sensitivity over the past 25 years, even though an extended growing season partially improved tree growth at high-elevation sites. In conclusion, all studied tree species were affected by drought events, even at humid high-elevation sites. Correlations with daily climate variables confirmed that even short-term weather conditions could strongly influence trees’ radial growth. Tree responses to climate conditions have shifted significantly between past and present periods but vary considerably among sites and are generally stronger in humid regions than in already dry areas.
Keywords: tree-ring widths; climate–growth relationships; forest dynamics; climate variability; extreme climatic events; Bavaria; Germany

Klimawandel, Waldökosysteme und BNE - Bräuning, Achim; Collier, Emily; Mölg, Thomas; Müller, Annette; Schubert, Jan Christoph; Thieroff, Bernhard (Praxis Geographie, 2019)

Permafrost Biases Climate Signals in delta O-18(tree-ring) Series from a Sub-Alpine Tree Stand in Val Bever/Switzerland - Grießinger, Jussi; Meier, Wolfgang; Bast, Alexander; Debel, Annette; Gaertner-Roer, Isabelle; Gaertner, Holger (Atmosphere, 2021)
During recent decades, stable oxygen isotopes derived from tree-ring cellulose (delta O-18(TRC)) have been frequently utilised as the baseline for palaeoclimatic reconstructions. In this context, numerous studies take advantage of the high sensitivity of trees close to their ecological distribution limit (high elevation or high latitudes). However, this increases the chance that indirect climatic forces such as cold ground induced by permafrost can distort the climate-proxy relationship. In this study, a tree stand of sub-alpine larch trees (Larix decidua Mill.) located in an inner alpine dry valley (Val Bever), Switzerland, was analysed for its delta O-18(TRC) variations during the last 180 years. A total of eight L. decidua trees were analysed on an individual base, half of which are located on verified sporadic permafrost lenses approximately 500 m below the expected lower limit of discontinuous permafrost. The derived isotope time series are strongly dependent on variations in summer temperature, precipitation and large-scale circulation patterns (geopotential height fields). The results demonstrate that trees growing outside of the permafrost distribution provide a significantly stronger and more consistent climate-proxy relationship over time than permafrost-affected tree stands. The climate sensitivity of permafrost-affected trees is analogical to the permafrost-free tree stands (positive and negative correlations with temperature and precipitation, respectively) but attenuated partly leading to a complete loss of significance. In particular, decadal summer temperature variations are well reflected in delta O-18(TRC) from permafrost-free sites (r = 0.62, p < 0.01), while permafrost-affected sites demonstrate a full lack of this dependency (r = 0.30, p > 0.05). Since both tree stands are located just a few meters away from one another and are subject to the same climatic influences, discrepancies in the isotope time series can only be attributed to variations in the trees' source water that constraints the climatic fingerprints on delta O-18(TRC). If the two individual time series are merged to one local mean chronology, the climatic sensitivity reflects an intermediate between the permafrost-free and -affected delta O-18(TRC) time series. It can be deduced, that a significant loss of information on past climate variations arises by simply averaging both tree stands without prior knowledge of differing subsurface conditions.
CRIS-Team WoS Importer:2021-08-06

The weather today rocks or sucks for my tree: exploring the understanding of climate impacts on forests at high school level through tweets - Mölg, Thomas; Schubert, Jan Christoph; Debel, Annette; Höhnle, Steffen; Steppe, Kathy; Wehrmann, Sibille; Bräuning, Achim (Geoscience Communication, 2024)
With the progression of global warming, impacts on the human sphere will undoubtedly increase. One promi- nent example at mid-latitudes is the stress on forests caused by climate change, which the BayTreeNet project (https: //baytreenet.de/, last access: 30 July 2024) addresses from an interdisciplinary viewpoint. Scientists from physical clima- tology, dendroecology, and educational research collaborate to examine how longterm changes in weather patterns affect the state of trees, and how the atmosphere–tree relation can be used to the advantage of improving the communication of climate change effects to, in particular, high school students. This article presents a 1-week case study for the sum- mer of 2021, when a distinct variability in weather patterns induced significant tree responses. The students of seven selected partner schools commented on the measured tree and weather data, which were available in real time, in the form of tweets and in conjunction with their educational geography program. The analyses of the tweets reveal that the stu- dents succeed in verbalizing the measured weather and, furthermore, manage to draw links between the stem diameter changes in trees and the weather variability. Problems arise with the use of less perceivable variables like the sap flow in the trees; also, the student posts exhibit shortcomings in establishing causal connections. Hence, the case study points to a discrepancy between describing basic environmental in- formation and appreciating or understanding the underlying mechanistic links. This point will serve to refine future classroom concepts and, moreover, to enhance the communication of climate change effects on forests to the general public.
Keywords: Climate Change; Geography Education; Research